Methods of Assessing Cattle Temperament and Factors Affecting it: a review - Smolinger, Jože; Škorjanc, Dejan (Agricultura Scientia, 2021)
In animal husbandry, the herd should consist of animals that are well adapted to a particular environment, which allows a safe working environment and the achievement of optimal production and economic results. Animals react differently to both positive and negative factors of the environment. Individual response to novel situations can affect metabolism as well as various physiological systems. A number of biochemical characteristics can be used as markers for assessing temperament. Temperament can also be defined as a combination of characteristics or qualities that form individual distinctive character. In this review article, we present various methods of assessing cattle temperament, firstly, in environments familiar to the animal, such as the barn and milking parlor, secondly, in unfamiliar special rooms or arenas with special equipment and, thirdly, considering other possible effects on the expression of temperament. Measurement of stress markers in saliva, feces, and hair using noninvasive methods has also been described as one of the approaches to assess temperament. Knowledge of cattle temperament allows us to work safely, introduce appropriate adapted breeding technologies, and improve housing conditions, which, consequently, results in improved animal welfare.
Keywords: cattle; behavior; temperament; assessment methods